Comparing the forecasting ability of financial conditions indices: The case of South Africa - Balcilar, Mehmet; Gupta, Rangan; van Eyden, Renee; Thompson, Kirsten; Majumdar, Anandamayee (Elsevier Science Inc, 2018)
In this paper we test the forecasting ability of three estimated financial conditions indices (FCIs) with respect to key macroeconomic variables of output growth, inflation and interest rates. We do this by forecasting the aforementioned macroeconomic variables based on the information contained in the three alternative FCIs using a Bayesian VAR (BVAR), nonlinear logistic vector smooth transition autoregression (VSTAR) and nonparametric (NP) and semi-parametric (SP) regressions, and compare the results with the standard benchmarks of random-walk, univariate autoregressive and classical VAR models. The three FCIs are constructed using rolling-window principal component analysis (PCA), dynamic model averaging (DMA) in the context of a time-varying parameter factor-augmented vector autoregressive (TVP-FAVAR) model, and a time-varying parameter vector autoregressive (TVP-VAR) model with constant factor loadings. Our results suggest that the VSTAR model performs best in the case of forecasting output and inflation, while a SP specification proves to be the best for forecasting the interest rate. More importantly, statistical testing for significant differences in forecast errors across models corroborates the finding of superior predictive ability of the nonlinear models. (C) 2018 Published by Elsevier Inc. on behalf of Board of Trustees of the University of Illinois.
Keywords: Financial conditions index; Dynamic model averaging; Nonlinear logistic smooth transition vector autoregressive model